A study of social sustainability practice in fashion accessories industry: Investigation of current practice and recommendations for future practice - Lee, Sunhee (2015)
Although there are a number of existing researches conducted regarding sustainability practice in fashion industry, it has been mostly limited to clothing industry within a broader concept with lack of empirical basis. This paper explores fashion accessories industry which has lack of exiting researches. The current study aims to discover in depth the current practice of social sustainability in fashion accessories providing the root causes of shortcomings of current sustainability. The paper reveals the disparities of definition and implication of sustainability for different stakeholders, which is underpinning idea that the current study goes further to suggest avenues for future research. This paper attempts to advance of understanding of practicing sustainability from practical viewpoints linking with existing theories from earlier scholars have released.